A randomized controlled trial of acupressure for the treatment of Raynaud's phenomenon: the difficulty of conducting a trial in Raynaud's phenomenon. Issue 2 (May 2016) - Gladue, Heather; Berrocal, Veronica; Harris, Richard; Tsou, Pei-Suen; Edhayan, Gautam; Ohara, Ray; Khanna, Dinesh
Objective: To examine the effect of acupressure on Raynaud's phenomenon (RP) in a randomized controlled clinical trial (RCT) and to evaluate the difficulties of conducting an RP RCT. Methods: A pilot single-center RCT of acupressure versus targeted patient education was conducted for the treatment of RP. Patients with either primary (n = 15) or secondary (n = 8) RP were randomized in an 8-week study. The primary endpoints included a decrease in the frequency and duration of RP. Secondary endpoints included several serum biomarkers including endothelial dysfunction, Raynaud's attack symptoms, Raynaud's Condition Score, and patient and physician global assessments of RP. Primary data analysis was conducted using the last observation carried forward and t -tests or a Wilcoxon rank test was used to compare the two groups. Results: Twenty-three patients were randomized and seven discontinued prematurely. Seventy-eight percent of patients were female, 96% were Caucasian, and the mean age was 49.8 (SD = 16) years. No statistically significant differences were detected between the acupressure versus education groups in primary and secondary outcomes (p>0.05). Frequency of attacks decreased by 6.7 attacks (SD = 8.8) in the acupressure group versus 7.2 (SD = 12.8) in the education group (p = 0.96), and the duration of attacks decreased by 11.4 (SD = 19.9) minutes in the acupressure group versus an increase of 0.8 minutes (SD = 11.2) in the education group (p = 0.14). There were no adverse events noted in the RCT. Conclusions: This pilot study does not support efficacy of acupressure for RP. Trial registration: ClinicalTrials.gov Identifier: NCT01784354.https://clinicaltrials.gov/ct2/show/NCT01784354?term=acupressure&rank=15